Estimating the limit possibilities of the step charging system for capacitive energy storage - Batygin, Yu. V.; Chaplygin, E. A.; Sabokar, O. S. (НТУ "ХПИ", 2016)
The basic diagram of the step-by-step charging system what is an alternative to the traditional variant with the step-up transformer was described. This system realizesthe serial charge voltage increasing by the separate portions of energy, which has been, accumulated preliminary in the inductive energy storage. The formulas for estimating the limit possibilities of the step-by-step charging were got. These limits are caused by achieving a balance of the entering and losing electromagnetic energy. The applicability of the formulas was illustrated by numerical examples.

Описана принципиальная схема ступенчатого заряда емкости, альтернативной традиционному варианту с повышающим трансформатором и предполагающей последовательное повышение зарядного напряжения за счёт подачи отдельных порций энергии, предварительно запасённой в обмотке специального индуктивного накопителя. Получены формулы для оценки предельных возможностей ступенчатого заряда, обусловленных достижением баланса в процессах поступления и потерь электромагнитной энергии. Применимость формул проиллюстрирована численными примерами.
Keywords: analytical analysis; electrical circuits; inductive energy storage; емкостной накопитель энергии; система ступенчатого заряда; аналитический анализ; электрические цепи